Enhancing Gardenia Leaf Nutrients via Shading, Vermicompost and Chelated Iron - Nuftji, Zainab Kamal Mustafa; Al -Bakkar, Alaa Husein A-Q. (Universitas Muhammadiyah Sidoarjo, 2024)
This study aimed to investigate the impact of shading, vermicompost, and chelated iron on the leaf content of certain elements in Gardenia jasminoides plants. Conducted at a private nursery in Erbil during the 2022 agricultural season, the experiment utilized gardenia plants propagated by cuttings and grafted onto one-year-old rootstocks. Over five months (April to October 2022), the effects of two shading levels (0% and 75% direct sunlight), vermicompost application at two levels, and chelated iron application at three levels (0, 0.1, and 0.2 g.L-1) were assessed. Results indicated that 75% shading significantly increased leaf nitrogen (1.72%) and iron content (73.94 mg.kg-1). Vermicompost at 25% significantly enhanced leaf nitrogen (1.75%), phosphorus (0.248%), potassium (1.36%), and iron (67.95 mg.kg-1). Chelated iron at 0.2 g.L-1 markedly improved leaf nitrogen (1.78%), phosphorus (0.256%), potassium (1.28%), and iron (78.45 mg.kg-1). The study utilized one-year-old uniform seedlings, grown in 15-liter pots with river loam soil, and standard care practices were followed. Data analysis was performed using ANOVA and Duncan’s Multiple Range Test at a 0.05 significance level. The findings suggest that specific shading, organic fertilizer, and chelated iron treatments can significantly enhance the nutrient content of gardenia leaves, potentially improving plant health and growth.